An open-loop photovoltaic-solar-thermal evacuated tube energy system for health clinics in Nigeria - Zwalnan, Selfa Johnson (2023)
The closed loop system photovoltaic solar thermal collector (PVT) is primarily conceived to cool the solar module for higher power production. One inherent problem with the closed loop configuration is the gradual loss of module efficiency with repeated circulation of the cooling water in a closed loop. This study, therefore, proposes a new hybridisation of the PVT collector with an evacuated tube based on an open-loop cooling strategy. The aim is to boost energy output and improve energy utilisation leading to reduce costs and improve economic viability. Therefore, a numerical model of the new system is formulated using TRNSYS 18 software. To assess the benefit of the proposed system, a numerical model of the conventional hybrid PVT closed-loop energy system is equally developed as benchmark, and the simulated performances of these systems are assessed and compared. A comparison of the new system's performance to the conventional system reveals that the solar fraction, is 0.74 and 0.80 for the basic and proposed systems, respectively. Similarly, the basic and proposed systems total collector efficiency was found to be 53% and 66% respectively. According to an economic analysis, the basic and new systems have Return on Investment (ROIs) of 33% and 14%, respectively. Even though the above results show that the proposed system outperformed the basic system based on the matrices used, it is also clear that the proposed system configuration and cooling strategy have met the goal of increasing net energy production and utilisation while minimising CO2 emissions in the energy mix far above the minimum acceptable technical standard of 30% solar fraction by National Renewable Energy Laboratory (NREL) for good profitability and environmental protection. This result is significant, exposing to individuals and investors, the business outlook of the new system. It equally a good roadmap for government to increase access to power in communities with poor grid access. The findings of this study are promising; however, this study could be expanded by using the parallel arrangement of the PVT.